Pengaruh Current Ratio, Return On Equity, Dan Debt To Equity Ratio Terhadap Harga Saham Pada Perusahaan Otomotif Dan Komponen Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2021 - Herni Lisawati (Universitas Batanghari Jambi, 2022)
In carrying out its operational activities, a company definitely needs a very large amount of funds. One effort that can be done is by selling company shares to investors. In investing their funds, Investors needs to assess the company’s performance,one way that can be done is by using financial rations. The purpose of this study is to determine and analyze the simultaneous and partial effect of the Current Ratio, Return On Equity, and Debt to Equity Ratio on stock prices in automotive and component companies on the Indonesia Stock Exchange for the 2015-2021 period. The object of this research is an automotive company listed on the IDX in 2015-2021 with a population of 13 companies. The sampling technique uses a purposive sampling technique where the number of samples is 5 companies. The analysis technique used in this study is multiple regression analysis. The results of the t test for the variable Current Ratio (X₁) obtained a significant value of (0.016 <0.05), which means that the Current Ratio (X₁) has a significant effect on stock prices (Y). While the variable Return On Equity (X₂) produces a significant value of (-0.956 > 0.05), which means that Return On Equity (X₂) has no significant effect on stock prices (Y). Furthermore, it can be seen that the variable Debt to Equity Ratio (X₃) has a significant value (0.003 <0.05) this means that the Debt to Equity Ratio (X₃) has a significant effect on stock prices (Y) Based on the F-test together the independent variables have a significant influence on the dependent variable. This can be proven from the calculated F value of 4.995 with a significance value (sig) of 0.006. Where is the Fcount value of 4.995 > Ftable of 2.90. Thus it can be said that the Current Ratio, Return On Assets and Debt Equity Ratio together have a positive and significant effect on stock prices.